Peculiarities of Formation of Runoff of the Upper Kolyma Basin (Osobennosti Formirovaniya Stoka na Rekakh Basseina Verkhnei Kolymy) - Kuznetsov,A. S.; Nasybulin,Sh. S. (1975)
The upper Kolyma basin is located in the zone of permafrost where the conditions for formation and regime of runoff are characterized by some singularity. The decisive factor in the formation of river runoff is the quantity of precipitation falling in the territory of the basin. It has been established by a study of the water balance for the rivers of this territory that the formation of runoff is dependent on the underlying surface. The greatest runoff is in rivers whose water collecting basins is covered by talus. Ice encrustations occur frequently in this area; these, however, do not increase runoff, but redistribute it in the course of a year. Where permafrost prevails, the losses of rain and meltwater have a temporary character in the acter layer. In the upper Kolyma basin evaporation from the soil varies in the range - 120-17- mm; this is approximately two to three times less than from the soil at the same latitudes in the European territory of the USSR. Draft trans. of Gidrometeorologicheskaya Observatoriya, Magadan, Sbornik Rabat (USSR) n3 p52-65 1970.